2010
DOI: 10.1007/s10545-010-9149-8
|View full text |Cite
|
Sign up to set email alerts
|

Whole body composition analysis by the BodPod air‐displacement plethysmography method in children with phenylketonuria shows a higher body fat percentage

Abstract: Background Phenylketonuria (PKU) causes irreversible central nervous system damage unless a phenylalanine (PHE) restricted diet with amino acid supplementation is maintained. To prevent growth retardation, a protein/amino acid intake beyond the recommended dietary protein allowance is mandatory. However, data regarding disease and/or diet related changes in body composition are inconclusive and retarded growth and/or adiposity is still reported. The BodPod whole body air-displacement plethysmography method is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 14 publications
5
52
0
Order By: Relevance
“…Others have found correlations between (fat-free) muscle mass and protein intake (Huemer et al 2007). As in other studies (Albersen et al 2010;MacDonald et al 2011), we saw a tendency to obesity in our cohort.…”
Section: Mri Morphological Findingssupporting
confidence: 87%
“…Others have found correlations between (fat-free) muscle mass and protein intake (Huemer et al 2007). As in other studies (Albersen et al 2010;MacDonald et al 2011), we saw a tendency to obesity in our cohort.…”
Section: Mri Morphological Findingssupporting
confidence: 87%
“…Consistent with our findings, a study in male Wistar rats indicates that GMP limits expansion of fat mass while maintaining lean mass (49). Given the rising incidence of overweight in children and adults with PKU (3,33), further investigation is warranted to determine the relevance of our findings to the treatment and/or prevention of obesity in patients with PKU.…”
Section: E892 Gmp Diet Modifies Metabolic Phenotype Of Pku Micesupporting
confidence: 86%
“…Our studies in humans with PKU (30,38,54) indicate that GMP improves protein retention, phe concentrations, and satiety and palatability of the low-phe diet. However, questions remain about the ability of GMP to support long-term growth, physiological function, and energy balance in those with PKU, especially given the rising incidence of overweight in children and adults with PKU treated with conventional AA diets (3,33).…”
mentioning
confidence: 99%
“…However, studies in several other non-US populations have not confirmed the tendency for PKU patients to become overweight nor have they found inherent differences in resting energy expenditure that would explain an increased risk for overweight in PKU patients [11,12]. Although no difference in body composition was found in pediatric PKU patients relative to a control population in an Austrian study [11], a more recent study detected a higher fat mass in Dutch pediatric PKU patients relative to controls [13].…”
Section: Introductionmentioning
confidence: 92%